KEDUDUKAN HUKUM CYBER CRIME DALAM PERKEMBANGAN HUKUM INTERNASIONAL KONTEMPORER - Maskun Maskun; Alma Manuputty; S.M. Noor; Juajir Sumardi (Masalah-Masalah Hukum, 2013)
Cybercrime is anewrange ofinternational law, particularlyinternationalcriminallaw. The existence ofcybercrimeis now afactthatshouldbe taken seriouslybythe international community.lmmediateresponseformto do is to regulate the cybercrime internationallybecausethe fact shows that no one convention has foundcybercrime internationally. The existed Convention of CyberC'iime enacts only regionally like European Convention of Cyber Crimeand locally (like in Indonesia), the Law number 11/2008 concerning Information and Electronic Transaction.